Intervención desde la teoría cognitiva para enfrentar la conducta bullying en los estudiantes del primer año de bachillerato del Colegio Remigio Geo Gómez Guerrero de la ciudad de Huaquillas, de la Provincia de El Oro, en el periodo lectivo 2014-2015. - Gómez Atto, Erika Alexandra (Machala : Universidad Técnica de Machala, 2015)
Desde un aspecto psicológico clínico, se realizó una investigación en el Colegio Remigio Geo Gómez Guerrero de la Ciudad de Huaquillas, que permita conocer la situación actual en la que se encuentra la institución con respecto a las conductas bullying entre los estudiantes y si existe un método de intervención para enfrentar este problema. Las conductas bullying son frecuentes en las instituciones educativas debido a que afecta de modo general el bienestar tanto físico como psicológico de los estudiantes deteriorando su rendimiento académico. Para la operalización de la investigación se utilizó métodos cualitativo- cuantitativo desde un enfoque epistemológico racional-deductivo, se aplicó encuestas dirigida a estudiantes y docentes de la institución. Se procesaron, analizaron y se compararon los datos obtenidos, lo que permitió conocer la realidad del objeto de investigación, lo que sirvió para diseñar la propuesta de intervención. De igual manera formular las conclusiones y las recomendaciones. La propuesta está dirigida desde un enfoque clínico, centrándose en proveer al profesional de mejores estrategias de intervención para enfrentar las conductas bullying en la institución, acción que repercutirá entre los estudiantes, docentes, familia y la sociedad.
From a psychological aspect clinical research was conducted at the College Remigio Gomez Guerrero Geo City Huaquillas that allows us to know the current situation in which the institution is located regarding bullying behaviors between students and the institution if there a method of intervention to address this problem. The bullying behaviors are prevalent in educational institutions because they generally affect both physical and mental well-being of students deteriorating academic performance. Qualitative-quantitative methods was used from a rational-deductive epistemological approach to the operationalization of the research, conducted surveys applied to students and teachers of the institution. They were processed and analyzed the data from the survey of students and teachers were compared, allowing know the reality of the research object, which is used to design the proposed intervention. Similarly formulate conclusions and recommendations. The proposal is directed from a clinical approach, focusing on providing the best professional intervention strategies to address bullying behavior in the institution, an action that resonate with students, teachers, family and society. From a psychological aspect clinical research was conducted at the College Remigio Gomez Guerrero Geo City Huaquillas that allows us to know the current situation in which the institution is located regarding bullying behaviors between students and the institution if there a method of intervention to address this problem. The bullying behaviors are prevalent in educational institutions because they generally affect both physical and mental well-being of students deteriorating academic performance. Qualitative-quantitative methods was used from a rational-deductive epistemological approach to the operationalization of the research, conducted 15 surveys applied to students and teachers of the institution. They were processed and analyzed the data from the survey of students and teachers were compared, allowing know the reality of the research object, which is used to design the proposed intervention. Similarly formulate conclusions and recommendations. The proposal is directed from a clinical approach, focusing on providing the best professional intervention strategies to address bullying behavior in the institution, an action that resonate with students, teachers, family and society.
Keywords: TEORIA; COGNITIVA; BULLYING; ESTUDIANTE